Strategic Analysis of Seaports using Multiple-Criteria Decision-Making Methods and TOWS - Jafari, Hassan; Jafari, Hamid; Loyes, Cheng (Journal of Asian Business Strategy, 2013)
Aim of This research is a Strategic analysis of seaports using multiple-criteria decision-making methods. At first, the strengths, weaknesses, opportunities and threats of Iranian seaports has been extracted from literature. Then, with respect to the importance concluded from LIKRET questionnaire distributed between experts (taking the views of the experts and specialist), five high importance factors of each strategic groups have been chosen and used in ANP analysis. When, all pricewise comparison have been done, the global weights of each factor calculated and then, four strategy alternatives have been determined with respect to the importance of each TOWS factors. Finally, after final calculation, the highest priority is assigned the SO strategy (Development of port and maritime transport facilities, utilizing modern technologies to develop transit trade in Iranian ports.), The ST strategy (Development of the trade, marketing, promotion and advertisement of transit corridors (North to south and Eastern transit corridors) passing through Islamic republic of Iran to promote the portion of domestic ports in export and import of foreign countries goods and cargoes via these ports) gained the second priority.